Alterations of the endocannabinoid system in adolescents with non-suicidal self-injury as a function of childhood maltreatment - Marc D. Ferger; Christine Sigrist; Susanne Brodesser; Michael Kaess; Julian Koenig (Translational Psychiatry, 2024)
Abstract Non-suicidal self-injury (NSSI) is a highly prevalent phenomenon in adolescence, often associated with prior traumatic experiences. The development and maintenance of NSSI is associated with dysregulation of the stress response, and evidence suggests that the hypothalamic-pituitary-adrenal (HPA) axis plays an important role. The endocannabinoid system is a neuromodulatory system in close functional interaction with the HPA axis. Several studies have reported alterations of the endocannabinoid system in adult patients with post-traumatic stress disorder. However, the role of the endocannabinoid system in children and adolescents with NSSI is less clear, and previously no study examined endocannabinoids in youth with experiences of maltreatment. N-arachidonyl ethanolamide (AEA) and 2-arachidonyl glycerol (2-AG) were quantified alongside sociodemographic and clinical characteristics in n = 148 adolescents (12–17 years of age). Analyses addressed group differences comparing healthy controls (HC, n = 38), patients with NSSI without (NSSI − CMT, n = 42) and with a history of childhood maltreatment (NSSI + CMT, n = 68). We show that AEA is reduced in adolescents with NSSI independent of childhood maltreatment. Further, we present first evidence for a negative association between AEA and NSSI frequency as well as AEA and the severity of childhood maltreatment. This is the first study providing evidence for alterations in the endocannabinoid system in children and adolescents engaging in repetitive NSSI. Findings from the study support current endocannabinoid-hypotheses on the neurobiology of trauma and adversity, extending existing findings of altered endocannabinoid signaling following exposure to traumatic events to a well-powered sample of children and adolescents.